A Nigerian tertiary institution students’ knowledge and attitude to mental health and services - Chinedu Arthur Idoko; Kenechukwu Udo; Chinelo Ifeoma Idoko (International Journal of Medicine and Health Development, 2021)
Background: Mental health and availability of its services are under-emphasized, misunderstood, and misplaced due to unfounded theories, mistaken beliefs, stigma, and fallacies, especially pronounced in the developing world. With these misconceptions come under-utilization of available services resulting in increased numbers of the mentally unhealthy in our society. This study aims at uncovering perceptions to the availability and effectiveness of mental health services as well as health-seeking behavior to such services. Materials and Methods: This study is a descriptive cross-sectional study. Respondents were picked by simple random sampling until a determined sample size was achieved. Pre-tested structured questionnaires were employed in data collection. The analysis was done with the Statistical Package for the Social Sciences (SPSS). Results: A greater percentage of respondents showed positive attitudes to mental health/services as 94.4% (321) of the respondents expressed that one had to be mentally healthy to function effectively; 66.2% (225) would seek orthodox mental health services if need be. Interestingly, a significant number (45.6%, 155) was unaware of availability of these services in Enugu even as findings revealed negative attitude toward the mentally ill, with 67.7% (230) of the view that the mentally ill should be avoided, whereas 71.7% (245) submitted that people with mental illness should not live in hostels. Conclusion: There is a need for improved/increased awareness on mental health spreading to the general populace as pronounced information gap exists even among university students.